A numerical study on non-Fourier heat conduction model of phase change problem with variable internal heat generation - Jitendra; Rai K.N.; Singh J. (My University, 2025)
In this study, the authors proposed one-dimensional non-Fourier heat conduction model applied to phase change problem in the presence of variable internal heat generation and this has been performed by finite element Legendre wavelet Galerkin method (FELWGM). We derived the stability analysis of the non-Fourier heat conduction model in our present case. The finite difference technique has been used to change the non-Fourier heat conduction model into an initial value problem of vector-matrix form and then we applied Legendre wavelet Galerkin method for the numerical solution of the present problem. The location of moving interface is analytically obtained under the steady-state condition. The effectiveness of the proposed numerical technique is verified through the experimental value of parameters which indicate promising results. In addition, the effect of Stefan numbers, internal heat generation, and its linear coefficient on the location of moving interface are discussed in detail and represented graphically. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.